Impact of genetically predicted atrial fibrillation on cancer risks: A large cardio-oncology Mendelian randomization study using UK biobank - Li, Wenjie; Huang, Mingkai; Wang, Rong; Wang, Wei (Frontiers in Cardiovascular Medicine, 2023)
Background: Rapidly increasing incidences of both atrial fibrillation (AF) and cancers have been observed over the recent years. However, the casual association of both serious conditions has been scarcely evaluated and considered to be a blank slate in cardio-oncology. Thus, we herein introduced Mendelian randomization (MR) methods to estimate the effects of AF on cancer risks. Methods: We performed univariable and multivariable two-sample Mendelian randomization (MR) analyses to evaluate the effects of AF on the risk of 14-specific site cancers. The present MR study was conducted based on 111 independent AF-associated genetic instruments from genome-wide association studies and summarized-level data from corresponding cancer consortia. Multiple sensitivity analyses including the leave-one-out analysis, MR-Egger regression and Cochran's Q test were further performed to examine potential directional pleiotropic effect. Functional annotation was performed for common differentially expressed genes of AF and prostate cancer (PCA). Results: A total of 5,617,489 European-descent individuals, including 462,298 cases and 5,155,191 controls, were included in the present MR analysis. Univariable MR analyses demonstrated a causal effect of AF on the incidence of PCA [odds ratio (OR): 0.96; 95% CI 0.92-0.99, p=0.01], and the causal effect remained significant (OR: 0.65; 95% CI 0.47-0.90, p=0.01) after adjusting for potential confounders through the multivariable MR approach. However, no casual associations between AF and other 13-spesific site cancer risks were observed (all p-values >0.05). Consistency of outcomes across complementary sensitivity MR methods further supported the causality. Functional analysis underlined the essential role of antioxidant and xenobiotic catabolic process in AF and PCA. Conclusion: Contrary to the findings of several previous observational studies, our comprehensive MR analyses did not corroborate a causal role for AF in increasing the risk of cancers. They did, however, demonstrate that AF may decrease the risk of PCA. Studies from larger sample size and individuals with different ethnic background were required to further support our conclusions.